Control of leaf blade outgrowth and floral organ development by LEUNIG, ANGUSTIFOLIA3 and WOX transcriptional regulators. Issue 4 (17th July 2019) - Zhang, Fei; Wang, Hui; Kalve, Shweta; Wolabu, Tezera W.; Nakashima, Jin; Golz, John F.; Tadege, Million
Summary: Plant lateral organ development is a complex process involving both transcriptional activation and repression mechanisms. The WOX transcriptional repressor WOX1/STF, the LEUNIG (LUG) transcriptional corepressor and the ANGUSTIFOLIA3 (AN3) transcriptional coactivator play important roles in leaf blade outgrowth and flower development, but how these factors coordinate their activities remains unclear. Here we report physical and genetic interactions among these key regulators of leaf and flower development. We developed a novel in planta transcriptional activation/repression assay and suggest that LUG could function as a transcriptional coactivator during leaf blade development. MtLUG physically interacts with MtAN3, and this interaction appears to be required for leaf and flower development. A single amino acid substitution at position 61 in the SNH domain of MtAN3 protein abolishes its interaction with MtLUG, and its transactivation activity and biological function. Mutations in lug and an3 enhanced each other's mutant phenotypes. Both the lug and the an3 mutations enhanced the wox1 prs leaf and flower phenotypes in Arabidopsis . Our findings together suggest that transcriptional repression and activation mediated by the WOX, LUG and AN3 regulators function in concert to promote leaf and flower development, providing novel mechanistic insights into the complex regulation of plant lateral organ development.